Integrative modelling of angiogenesis in the bovine corpus luteum - Prokopiou, Sotiris (2013)
The corpus luteum (CL) is a tissue formed from the remnants of an ovulated follicle in the ovary, and it produces the progesterone needed for a healthy pregnancy. CL growth is highly dependent on a growing nutrient supply, and can be compared with the most aggressive vascular tumours. Angiogenesis, the growth of new blood vessels from existing ones, plays a key role in the growth and function of the CL. Inadequate angiogenesis has been linked to infertility in cows. The CL is composed of several vascular(e.g. endothelial cells (ECs), pericytes (PCs)), and avascular (e.g. luteal cells (LCs), immune cells) cell types, and several pro-angiogenic factors (e.g. Fibroblast Growth Factor 2, FGF2) found to be important in the angiogenic process.